2016
DOI: 10.1097/md.0000000000003890
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 51 publications
1
45
0
Order By: Relevance
“…[ 4 , 8 , 9 ] This rare neoplasm seems to arise most commonly at retroperitoneal, visceral, abdominal, and pelvic sites but has been reported at almost every body site, and the growing list of reported sites include gastrointestinal, gynecologic, and genitourinary sites, the extremities, somatic soft tissue, and the skin; among these sites are the falciform ligament, uterus, uterine cervix, liver, kidney, lung, breast, cardiac septum, pancreas, prostate, thigh, and gastrointestinal tract. [ 1 , 9 13 ] These tumors all share a distinctive cell type, the PEC, which has no known normal tissue counterpart. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 4 , 8 , 9 ] This rare neoplasm seems to arise most commonly at retroperitoneal, visceral, abdominal, and pelvic sites but has been reported at almost every body site, and the growing list of reported sites include gastrointestinal, gynecologic, and genitourinary sites, the extremities, somatic soft tissue, and the skin; among these sites are the falciform ligament, uterus, uterine cervix, liver, kidney, lung, breast, cardiac septum, pancreas, prostate, thigh, and gastrointestinal tract. [ 1 , 9 13 ] These tumors all share a distinctive cell type, the PEC, which has no known normal tissue counterpart. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was a marked female preponderance. [ 9 , 12 , 13 ] In 2016, Chen et al [ 13 ] reported in a review study of gastrointestinal PEComa that the gastrointestinal tract is the second most frequent site of PEComa, with the most frequent site being the gynecological tract. They further indicated that gastrointestinal PEComas of the colon and rectum were most common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age of the patients at the time of PEComa diagnosis is most commonly in the range of 38.9-56 years [7,8], but PEComa cases in children have also been described [9,10]. All reviews indicate more common PEComa occurrence in women (54-86.9% of cases) [11,12], also after exclusion of sex-specific locations from the analysis [3].…”
Section: Epidemiologymentioning
confidence: 99%
“…The basic pathological differential diagnosis for PEComa NOS (summarised in Table 1) encompasses: gastrointestinal stromal tumours (GIST), melanoma, renal cell, and adrenocortical carcinoma, especially the chromophobic type, clear cell sarcoma of tendon and aponeurosis -melanoma of the soft parts (CCS), alveolar soft part sarcoma (ASPS) [8,52], paraganglioma, angiomyolipoma, and also gynaecological tumours such as endometrial stromal sarcoma with clear cell features or uterine tumour resembling sex cord tumour and other tumours with a clear cell component [4]. It is also important to distinguish them from tumours derived from smooth muscle (epithelioid leiomyosarcoma -LMS and epithelioid leiomyoma).…”
Section: Pathomorphologymentioning
confidence: 99%